Audit of Typical Prescription Format Among the Prescribers of a Garment Medical Centre in Bangladesh (Update Dental College Journal, 2013)
Objective: To audit the typical prescription or general format according to WHO guidelines for good prescription writing.Materials and methods: A cross-sectional descriptive study was conducted after collecting data from medical records to observe standard of prescriptions and identify factors underlying inappropriate prescription writing.Place and period of study: A total of 300 prescriptions of the patients (garment workers) who had attended in Hannan Textile and Garment Medical Centre, Board Bazar, Dhaka, Bangladesh in between January and November2008 were considered for analysis. Results: Audit of the prescription pattern revealed that most of the prescriptions did not conform to the pattern of a typical prescription. The patients identity was mentioned in all prescriptions (100%). Date of the prescription and superscription symbol (Rx) were also mentioned in all prescriptions (100%). Inscription which includes name of the drug, dosage form and total amount of medication prescribed was mentioned in all prescriptions (100%) but dose and duration of treatment were mentioned in 66% and 70% prescriptions respectively. In this study, about 91.67% instructions to the pharmacist and 50% special instructions to the patient regarding the dosage form and total amount to be dispensed were found adequately. Almost 100% of the prescriptions adequately mentioned the dosage schedules and also precautions/warnings about the drug therapy. Almost 100% of the prescriptions were signed by the doctors mentioning their full name, address with qualification and registration number. But telephone/mobile number of the doctors was not found in all prescriptions (100%). Most common diagnosis among garment workers was ARI (19.33%). Most commonly prescribed group of drug was antiulcerent (17.13%) and most commonly prescribed antibiotic was amoxicillin (13.67%). Most of the drugs were prescribed in oral form (97.77%). No single drug interaction (0%) was found in any prescription. The fixed dose-drug combinations (FDCs) accounted for 67% drugs prescribed. The most commonly FDC was multivitamin and multimineral which was not included in essential medicine list (EML).Conclusion: Large numbers of prescriptions did not conform to ideal pattern and lack in their rationality. This study revealed a lot of scope for educating the prescribers to improve prescribing practices.DOI: http://dx.doi.org/10.3329/updcj.v1i2.13979 Update Dent. Coll. j. 2011: 1(2): 07-12